LEGAL SECURITY IN INDONESIA, THE BIGGEST CHALLENGE OF MEA - Indrastuti, Lusia (PROCEEDING INTERNASIONAL SEMINAR, 2015)
ASEAN Economic Community 2015 or Masyarakat Ekonomi ASEAN (MEA) will be established starting on December 31, 2015. The impact is that the opportunity in free trade of service and goods among ASEAN countries is widely open. In facing MEA, especially in Indonesia, supports from many different parties are needed, such as the business persons, government, community, and of course law becomes one of the props in running the economy in the country.Several problems and challenges that Indonesia currently face in implementing MEA namely are: there is lack of legal security for the business owners to ensure them to keep investing their business, the lack of readiness of businessmen in making agreements between themselves, slow service of bureaucracy and government commitment, and also the need of judiciary institution that can provide justice to all parties. Legal security is created through effective rules support, good faiths of the businessman, and law enforcers that fully support MEA since legal security in MEA is an absolute requirement.Key words: MEA, Law, Legal Security